2013
DOI: 10.1007/s10517-013-2297-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell Therapy of Refractory Crohn’s Disease

Abstract: We analyzed medium-term efficiency and safety of biological therapy of Crohn's disease, in particular transplantation of allogenic mesenchymal stromal bone marrow cells and anticytokine therapy with selective immunosuppressive agents. It was found that both methods of biological therapy of refractory Crohn's disease resulted in clinical and in some cases endoscopic remission. In most cases, clinical remission was maintained without steroid hormone therapy. Thus, both methods produce comparable clinical results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Both hematopoietic and mesenchymal stem cells (MSCs) have shown good results when they induced a long-lasting clinical remission in severe cases of CD. 115 …”
Section: Signaling Pathways Mediated By Cytokinesmentioning
confidence: 99%
“…Both hematopoietic and mesenchymal stem cells (MSCs) have shown good results when they induced a long-lasting clinical remission in severe cases of CD. 115 …”
Section: Signaling Pathways Mediated By Cytokinesmentioning
confidence: 99%
“…Over the past decade, the immunomodulatory functions of MSCs have triggered great interest in their application toward treating various immune disorders, including graft‐versus‐host disease (GVHD), transplanted organ rejection, and autoimmune diseases . While previous large‐scale clinical trials using MSCs therapy had inconclusive results , it is possible that these results are due to the varied cytokine environments MSCs encounter in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that MSCs also exhibited potential roles for anti-inflammatory functions [ 40 ]. Thus, MSCs have been employed as therapeutic strategies for various immune disorders including graft-versus-host disease (GVHD) [ 41 43 ], organ transplantation [ 44 47 ], autoimmune diseases [ 48 52 ] and inflammatory bowel disease [ 53 , 54 ]. Indeed, MSCs interact with T cells to reduce their pro-inflammatory cytokine production [ 36 , 55 ], while increasing their production of anti-inflammatory cytokines, including IL-4 and IL-10 [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%